2001
DOI: 10.1177/009164710102900205
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Needs and Resources in Christian Communities of South Korea

Abstract: In an effort to understand the mental health needs and resources of Korean Christians, we collected quantitative and qualitative data through surveys and interviews with Korean pastors and Christian educators. Several mental health concerns were identified: the high level of daily stress faced by many Koreans, marriage and family concerns, conflicts between Korean culture and the teachings of the church, and a tendency to keep emotional discomfort suppressed. Mental health resources include deep spiritual comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…KA churches are an important setting for health promotion, health education, and communitybased research for KA immigrant families. McMinn et al (2001) found that pastors in Korea often could not differentiate between psychological and spiritual problems, and most Korean pastors did not encourage the use of mental health services. Through collaborative efforts with KA churches, both mental health providers and KA pastors can be better equipped to meet the needs of KA immigrants and reduce the perceived stigma associated with having a mental health problem and seeking mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…KA churches are an important setting for health promotion, health education, and communitybased research for KA immigrant families. McMinn et al (2001) found that pastors in Korea often could not differentiate between psychological and spiritual problems, and most Korean pastors did not encourage the use of mental health services. Through collaborative efforts with KA churches, both mental health providers and KA pastors can be better equipped to meet the needs of KA immigrants and reduce the perceived stigma associated with having a mental health problem and seeking mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Developing any new specialty area in professional psychology is, to a large extent, a research task. By describing various CCPC research activities in this article and elsewhere (Chaddock & McMinn, 1999; Edwards et al, 1999; Ellens et al, 2000; McMinn et al, 1998; McMinn et al, in press), we hope to generate interest in church–psychology collaboration as an important area of research for scholars, professional psychologists, and doctoral students.…”
Section: Discussionmentioning
confidence: 99%
“…How have clergy and psychologists effectively overcome trust barriers to establish effective working relationships (Aikins, 2000)? What are the needs for clergy–psychologist collaboration in various cross-cultural contexts (Ellens, McMinn, Lake, Hardy, & Hayen, 2000; McMinn et al, in press)? What information from psychology would clergy find useful in their daily work (McRay, McMinn, Wrightsman, Burnett, & Ho, in press)?…”
Section: Center For Church–psychology Collaboration (Ccpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the need for psychological training in less developed countries, psychologists and other mental health professionals from the United States have been involved increasingly in international training and service ventures. These endeavors include assessment of mental health needs (Ellens, McMinn, Lake, Hardy, & Hayen, 2000; Levers, 1997; McMinn, Roh, et al, 2001), providing of direct services (Mwiti & Gatewood, 2001; Pedulla & Pedulla, 2001; Weine et al, 2002), and training of local mental health providers and instructors (Bacigalupe, 1998; Bacigalupe & Fuks, 1998; Inger, 1998; McMinn, Meek, Canning, & Pozzi, 2001; Weine et al, 2002). An example of this can be found in an earlier Professional Psychology article in which Pedulla and Pedulla (2001) described an innovative model for cross-cultural service provision.…”
mentioning
confidence: 99%